Shift work and age as interactive predictors of body mass index among offshore workers - Parkes, Katherine R (Scandinavian Journal of Work, Environment & Health, 2002)
' ' OBJECTIVES ': 'This study investigated shift pattern (day shifts versus day-night rotation) and its interactions with age, and with the years of shiftwork exposure, as predictors of body mass index (BMI). ' ' METHODS ': 'Survey data were collected from offshore personnel working day shifts (N=787) or day-night shifts (N=787); information was obtained about shift pattern and years of shiftwork exposure, height, weight, demographic factors, and smoking habits. Hierarchical multiple regression was used to test a model in which BMI was predicted by additive and interactive effects of shift pattern, age, and exposure years with control for confounding variables. ' ' RESULTS ': 'In a multivariate analysis (controlling for job type, education and smoking), BMI was predicted by the main effects of age (P<0.001) and years of shiftwork exposure (P<0.02). Shift pattern was not significant as a main effect, but it interacted significantly with the curvilinear age term (P<0.025) and with the linear (P<0.05) and curvilinear (P<0.05) components of shiftwork exposure. In the day group, age but not exposure predicted BMI; the opposite was true of the day-night group. The D-N group showed a steeper increase in BMI with an increase in age and exposure years than the day group did. ' ' CONCLUSIONS ': 'The significant interaction effects found in this study were consistent with the view that continued exposure to day-night shift work gives rise to increases in BMI, over and above the normative effects of ageing on BMI shown by day shiftworkers.
Keywords: age; body mass index; body weight; demographic factor; health behavior; job type; night work; occupation; offshore worker; shift work; smoking